INFLUENCE OF INTEGRATED MARKETING COMMUNICATION TO BRAND AWARENESS AND BRAND IMAGE TOWARD PURCHASE INTENTION OF LOCAL FASHION PRODUCT - Nahda Ihzaturrahma; Nurrani Kusumawati, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
Many young Indonesian entrepreneurs have opened clothing brands to introduce local fashion products that are not inferior to other well-known brands. Business owners are still confused about how they can increase brand awareness and brand image through effective information dissemination methods. This really affects several things in the business they have, such as sales, followers on social media, consumers, etc. Therefore, this research aims to identify Integrated marketing communications methods can affect brand awareness and brand image toward the purchase intention of local fashion products by using smart PLS analysis. This time, the object of the questionnaire this time is using a local brand from Dama Kara. Six hypotheses are proposed based on the needs you want to analyse and a quantitative approach was adopted with 215 respondents. This study confirmed that one of the most influential factors on purchase intention towards local fashion products is sales promotion, in which people will purchase local fashion products if they get many promotions that are offered from the local fashion brand they want to buy. According to the data processing results, there are two aspects that influence brand image and brand awareness: advertising and sales promotion. Thus, this finding highlights the need to analyse many local fashion brands in Indonesia more deeply and more specifically so that they can find out the problems that occur in each local fashion brand in Indonesia and get perspectives from various consumers from various local fashion brands. These findings from this research will be used as a recommendation for the Look at Me brand to develop a sustainable marketing strategy for the more specific Indonesian target market with methods from integrated marketing communication.